Transition from the chaotic turbulence to the turbulent structures - A. Kingsep (Discrete Dynamics in Nature and Society)
Weak turbulence, similar to incoherent light, may be represented as an ensemble of quasi-free quanta or Fourier harmonics. Unlike it, strongly turbulent state should be based on nonlinear structures. In particular, strong plasma turbulence may be constructed of discrete formations, viz., Langmuir solitons. Instead for ‘infrared catastrophe’ typical of the weakly turbulent regime, one deals with the ‘relay race’ model providing the proper direction of the energetic flux over scales from the source towards the leakage.